Core/shell structure of Ni/NiO encapsulated in carbon nanosphere coated with few- and multi-layered graphene: synthesis, mechanism and application - Ghaemi, Ferial; Abdullah, Luqman Chuah; Tahir, Paridah (MDPI, 2016)
This paper focuses on the synthesis and mechanism of carbon nanospheres (CNS) coated with few- and multi-layered graphene (FLG, MLG). The graphitic carbon encapsulates the core/shell structure of the Ni/NiO nanoparticles via the chemical vapor deposition (CVD) method. The application of the resulting CNS and hybrids of CNS-FLG and CNS-MLG as reinforcement nanofillers in a polypropylene (PP) matrix were studied from the aspects of mechanical and thermal characteristics. In this research, to synthesize carbon nanostructures, nickel nitrate hexahydrate (Ni(NO3)2·6H2O) and acetylene (C2H2) were used as the catalyst source and carbon source, respectively. Besides, the morphology, structure and graphitization of the resulting carbon nanostructures were investigated. On the other hand, the mechanisms of CNS growth and the synthesis of graphene sheets on the CNS surface were studied. Finally, the mechanical and thermal properties of the CNS/PP, CNS-FLG/PP, and CNS-MLG/PP composites were analyzed by applying tensile test and thermogravimetric analysis (TGA), respectively.